The Church in the face of nomads at the turn of the 4th and 5th centuries - Ilski, Kazimierz (Balcanica Posnaniensia. Acta et studia, 2007)
The author addresses the issue of late antique Christianity's attitude towards the peoples migrating to the borders of the Roman Empire. The aim of the article is to show how reflections on barbarians developed in the writings of the Church Fathers and late antique authors: from extremely negative assessments (Synesius of Cyrene, Ambrose, Jerome) to more open and universalistic interpretations (Temistius, Augustine, Orosius). The analysis is based on literary sources – theological treatises, sermons, letters, panegyrics and historical writings in which religious ideas are intertwined with the political and social realities of the era. The research method consists of a critical analysis of ancient texts, taking into account their rhetorical, ideological and historical context. The author points out that the Church's attitude towards barbarians was not uniform. Alongside apocalyptic accents, interpreting the invasions as a harbinger of the end of the world, there were concepts emphasising that Christianisation and acculturation were to enable coexistence with the immigrant population. Due to its universalist mission, the Church was more open to the assimilation of foreigners than the Empire itself. Ultimately, it was the vision of the unity of many nations within the Christian community that became the dominant perspective, although it did not completely eliminate fear and aversion towards nomads.